A challenging case of Francisella Tularensis: teenager's massive lymphoadenopathy caused by an uncommon infectious disease. - G. Castellana; M. Ciuffreda; E. Pisello; U.W. Basso; J. Silvestri; M. Caimmi; A. Pennacchi; D. Galante; C. Piangatelli (Pediatric Anesthesia and Critical Care Journal, 2022)
Tularemia is a potentially fatal, multisystemic infectious disease of humans and some animals caused by Fran- cisella Tularensis bacteria. Up to six forms of clinical manifestations of tularemia have been identified, ulcer- oglandular tularemia being the most common form. Up- per airway manifestations of tularemia include tonsillar hypertrophy and pharyngitis, accompanied by cervical lymphadenopathies. Anatomical alterations of the cervi- cal district represent an additional risk in airways man- agement. Between 2016 and 2019, only three cases of tu- laremia have been described in Italy, but some authors consider Tularemia underreported, especially in Europe. We describe a case of a 17-year-old boy who presented to our clinic with massive cervical left lymphadenopathy and enlargement of the ipsilateral palatine tonsil associ- ated with fever. The symptoms persisted after antibiotic and corticosteroid treatment. To exclude a lymphoprolif- erative disease, a full body CT scan with contrast was performed, showing multiple cervical bilateral lymphadenopathies, especially on the left side and hyper- trophy of the left palatine tonsil and splenomegaly. The biopsy of the left tonsil, performed under general anes- thesia, demonstrated a granulomatous inflammation. A more accurate reconstruction of the patient history re- vealed domestic presence of rabbits. Therefore, serologic and molecular tests for F. Tularensis were performed, with positive results. Proper antibiotic treatment was ad- ministered with gradual and complete symptoms regres- sion.